Debating E-voting throughout Europe: constitutional structures, parties' concepts and Europeans' perceptions - Borucki, Isabelle; Hartleb, Florian (Frontiers in Political Science, 2023)
Techno-optimists with a more cosmopolitan focus agree that E-voting lies at the heart of implementing e-government and digitalisation into democratic structures. However, we do not know much about the extent to which E-voting exists in European constitutions, even after one generation of intense debate about its possible implementation. Perceptions of E-voting matter because of the omnipresent digital transformation and discussions about how democracies (could) digitalise. How do party policies resemble E-voting on the national and European levels? E-voting represents a bottom-up part of top-down e-government and, through this, digital transformation. The example of the “e-state” Estonia proves the relevance: E-voting has been in (legal) practise since 2005, and research can take much empirical evidence from this laboratory for digital innovation. The fact that Estonia is an exception to the rule within the EU member states explains the comparative approach to the (possible) legal framework for e-participation. With focussing on liberal democracies' constitutional predefinitions, voting procedures in the virtual age have not been compared yet. We approach the question of “legalistic opportunity structures” by relying on constitutions of European member states, parties' policies, and survey data from Eurobarometer. Using a dictionary approach, our research design analyses the constitutions and manifestos of parties running for the European elections, combined with a classic analysis of surveys. Therefore, national constitutions and party manifestos are part of this study, which we analyse using several mixed methods approaches and confront them with survey outcomes. Our results have the broader implications that we need to study in more detail what the digital transformation and the constitutionalisation of electronic decision-making entail to develop a digital democracy and link it to a public sphere throughout Europe. In the end, we conclude by analysing whether the EU pushes its member states to E-voting and will implement E-voting for European elections.